2013
DOI: 10.1111/fare.12006
|View full text |Cite
|
Sign up to set email alerts
|

Linking Changes in Couple Functioning and Parenting Among Couple Relationship Education Participants

Abstract: The current study represents a novel test of parenting outcomes among participants in couple and relationship education (CRE). Utilizing a systems theory framework and empirical linkages between couple functioning and parenting, this study examined the extent to which several parenting dimensions (coparenting conflict, parental involvement, and positive discipline practices) change after CRE participation and, importantly, whether and how these changes are related to changes in dimensions of couple functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 54 publications
(80 reference statements)
3
34
0
Order By: Relevance
“…During the 1990s and continuing to the present day, researchers influenced by family systems principles began to examine the correlations among parenting effectiveness, distress between the parents, and children's outcomes (Cummings & Davies, 1994; Grych, Fincham, Jouriles, & McDonald, ). More recent studies replicate and extend the early conclusions: In both middle‐class (P. Cowan & Cowan, ; Harold, Elam, Lewis, Rice, & Thapar, ) and low‐income (Adler‐Baeder et al, ; Conger, Cui, & Lorenz, ) families, when parents are more collaborative and able to resolve their differences, mothers and fathers are observed to have warmer, more sensitive, and appropriate limit‐setting interactions with their children or adolescents; in turn, the children score higher on academic achievement tests and are described by research staff and teachers as having fewer behavior problems than children of parents with more combative relationships.…”
Section: A Brief History Of Research and Theory Supporting Our Familymentioning
confidence: 60%
“…During the 1990s and continuing to the present day, researchers influenced by family systems principles began to examine the correlations among parenting effectiveness, distress between the parents, and children's outcomes (Cummings & Davies, 1994; Grych, Fincham, Jouriles, & McDonald, ). More recent studies replicate and extend the early conclusions: In both middle‐class (P. Cowan & Cowan, ; Harold, Elam, Lewis, Rice, & Thapar, ) and low‐income (Adler‐Baeder et al, ; Conger, Cui, & Lorenz, ) families, when parents are more collaborative and able to resolve their differences, mothers and fathers are observed to have warmer, more sensitive, and appropriate limit‐setting interactions with their children or adolescents; in turn, the children score higher on academic achievement tests and are described by research staff and teachers as having fewer behavior problems than children of parents with more combative relationships.…”
Section: A Brief History Of Research and Theory Supporting Our Familymentioning
confidence: 60%
“…From this perspective, what places children at risk for negative outcomes lies not in the structure of the family itself but rather in the atmosphere of the family environment and the quality of relationships established among family members both pre‐ and post divorce. Examples include literature on the intergenerational transmission of parental sensitivity and secure attachment (van IJzendoorn, ) and the management of interparental conflict and children's behavior problems (Adler‐Baeder et al, ).…”
Section: Looking Back: Different Perspectives For Interpreting Familymentioning
confidence: 99%
“…Evidence from applied research also suggests that including couple skills training with parenting skills training may result in more positive parenting practices (e.g., Cowan, Cowan, Pruett, Pruett, & Wong, ). Recently, a few RE evaluations have also modeled this spillover effect and found that changes in the couple domain were associated with change in the parenting domain (Adler‐Baeder et al., ), and that enhancing the couple or coparenting relationship was beneficial to child outcomes (Kirkland et al., ). The current study adds to this evidence with a different population.…”
Section: Discussionmentioning
confidence: 99%